2011
DOI: 10.1042/bst0390259
|View full text |Cite
|
Sign up to set email alerts
|

In vitroproof of direct regulation of glutamine synthetase by GlnK proteins in the extreme halophilic archaeonHaloferax mediterranei

Abstract: Haloferax mediterranei is an extreme halophilic micro-organism belonging to the Archaea domain that was isolated from the Santa Pola solar salterns (Alicante, Spain) in 1983. The biochemistry of the proteins involved in nitrogen metabolism is being studied, but the knowledge of their regulation is very scarce at present. The PII superfamily is constituted by major regulators of nitrogen metabolism, which are widespread in prokaryotic and eukaryotic organisms. These trimeric proteins (12 kDa per subunit) have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 24 publications
(29 reference statements)
6
14
0
3
Order By: Relevance
“…The levels of amtB‐glnK transcripts agree with our previous study in which GlnK levels were only detected by anti‐GlnK immunoblot under nitrate‐rich conditions when cells were starved for ammonium (Pedro‐Roig et al. ). The a mtB1‐glnK1 and amtB2‐glnK2 probes of this study share DNA sequence homology, making it difficult to assess whether both gene pairs are transcribed.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The levels of amtB‐glnK transcripts agree with our previous study in which GlnK levels were only detected by anti‐GlnK immunoblot under nitrate‐rich conditions when cells were starved for ammonium (Pedro‐Roig et al. ). The a mtB1‐glnK1 and amtB2‐glnK2 probes of this study share DNA sequence homology, making it difficult to assess whether both gene pairs are transcribed.…”
Section: Resultssupporting
confidence: 91%
“…This nitrogen‐regulated expression was in good agreement with the profiles observed for glnK1‐amtB1 transcript (see above) and GlnK protein (Pedro‐Roig et al. ). The results suggested that AmtB1 could be produced in Hfx.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations